New Insights Into the Evolutionary History of Melatonin Receptors in Vertebrates, With Particular Focus on Teleosts - Maugars, Gersende; Nourizadeh-Lillabadi, Rasoul; Weltzien, Finn-Arne (Frontiers in Endocrinology, 2020)
In order to improve our understanding of melatonin signalling, we have reviewed and revised the evolutionary history of melatonin receptor genes (mtnr) in vertebrates. All gnathostome mtnr genes have a conserved gene organization with two exons, except for mtnr1b paralogs of some teleosts that show intron gains. Phylogeny and synteny analyses demonstrate the presence of four mtnr subtypes, MTNR1A, MTNR1B, MTNR1C, MTNR1D that arose from duplication of an ancestral mtnr during the vertebrate tetraploidizations (1R and 2R). In tetrapods, mtnr1d was lost, independently, in mammals, in archosaurs and in caecilian amphibians. All four mtnr subtypes were found in two non-teleost actinopterygian species, the spotted gar and the reedfish. As a result of teleost tetraploidization (3R), up to seven functional mtnr genes could be identified in teleosts. Conservation of the mtnr 3R-duplicated paralogs differs among the teleost lineages. Synteny analysis showed that the mtnr1d was conserved as a singleton in all teleosts resulting from an early loss after tetraploidization of one of the teleost 3R and salmonid 4R paralogs. Several teleosts including the eels and the piranha have conserved both 3R-paralogs of mtnr1a, mtnr1b and mtnr1c. Loss of one of the 3R-paralogs depends on the lineage: mtnr1ca was lost in euteleosts whereas mtnr1cb was lost in osteoglossomorphs and several ostariophysians including the zebrafish. We investigated the tissue distribution of mtnr expression in a large range of tissues in medaka. The medaka has conserved the four vertebrate paralogs, and these are expressed in brain and retina, and, differentially, in peripheral tissues. Photoperiod affects mtnr expression levels in a gene-specific and tissue-specific manner. This study provides new insights into the repertoire diversification and functional evolution of the mtnr gene family in vertebrates.